Robotic Process Automation: Under Promise Over Deliver - Bedekar, Shantanu; Satpathy, Diptikanta (Indian Journal of Computer Science, 2019)
Today, humanity is witnessing a transformational era in the history of mankind. Needless to say, the acceleration of change in technology is faster than ever before. Changes in technology in a year are more than what changed over decades earlier. Riding on technological advancements, customer expectations are going northward, and they are expecting more every day. Customers want quality service with reduced delivery time without spending more. Manufacturers and service providers are searching for opportunities and betting big on technology to reduce costs and improve quality through reduction of defects. Automation had always been the tool to achieve this. Traditionally technology has focused on automation by mechanical robots. Robots have taken over entire shop-floor and warehouse tasks. Now robots are entering office space to perform routine mundane activities to execute business transactions. In common parlance, it is known as Software Robotic Process Automation (RPA). The article discusses about this transformation technology platform that is reshaping how corporations run business. RPA has the potential to impact all aspects of business from customer facing functions to finance backroom operations, from purchasing to manufacturing operations, and from planning to data maintenance. RPA stands to greatly benefit many enterprises dealing with repetitive, rule-based activities performed by system users across IT platforms using structured and unstructured data. It leaves humans to focus more on value-adding activities that require judgement, speculation, and intelligence. The use cases in this article are examples from real business applications which the authors are involved to a great extent, from feasibility and process study to implementation. For more information, they would be glad to be contacted.